(untitled) (Research, Society and Development, 2021)
Early childhood caries or Early Childhood Caries (CPI) is a multifactorial disease with rapid and severe progression. It occurs during early childhood and is mainly influenced by the microbiota and cariogenic diet. Several treatments are proposed, depending on the extent of the carious lesions, ranging from the topical application of fluoride to more invasive treatments, such as tooth extraction and orthodontic rehabilitation. It is a disease that affects underprivileged patients reaching severe stages when untreated, has unknown etiology by parents where they do not notice the development of the first clinical signs, seeking late dental care when the patient has pain and discomfort in chewing on the affected side. It has been noted that CPI has percussions that affect the quality of life and can compromise the child’s growth and development. Caries is, however, a preventable disease once the factors that lead to its development become known. Inadequate eating habits are the main risk factors, the host’s diet can be seen as the primary factor in determining susceptibility to the disease. It is concluded that dental caries (CD) is a tooth deterioration strongly influenced by the individual’s lifestyle.